Pengelolaan Kelas Dalam Pembelajaran IPS Terpadu Pada Kurikulum 2013 Di SMP Negeri 1 Batangan Kelas VII Tahun Ajaran 2015/2016 (Studi Etnografi di SMP Negeri 1 Batangan) - Sharin, Lolita Viningka Selma, Prof. Dr. Harsono, SU (2016)
Lolita Viningka Selma Sharin / A210120065. MANAGEMENT CLASS IN LEARNING INTEGRATED SOCIAL STUDIES CURRICULUM IN 2013 IN SMP NEGERI 1 BATANGAN CLASS VII ACADEMIC YEAR 2015/2016 (Ethnographic Studies in SMP Negeri 1 Batangan). Thesis. The Faculty of Education, University of Muhammadiyah Surakarta, May,2016. This aimed research are describe classroom management in learning Integrated IPS using curriculum 2013 focused on characteristics classroom setting for the management of effective learning and the characteristics of the learning relationship between teachers and learners in social studies using the Integrated curriculum in 2013. Type of research is qualitative research and an ethnographic design. The informant is the principal, vice principal curriculum areas and seventh grade social studies teacher. Data collection techniques used indept interview, observation and documentation. The validity of the data used triangulation techniques. Research result (1) characteristics of the class setting for learning management Effective include seating learners U-shaped letter, their teaching tools and fittings or the use of learning media has been good and tidy in accordance with the method used by teachers in each delivery of material, the creation of structuring the cleanliness and beauty of a good class. 2) the characteristics of the learning relationship between teachers and students in social studies Integrated using the curriculum in 2013 among others the relationship between teachers and learners well established interaction and the teacher as a facilitator for learners, complement the role of the teacher, guide, and direct the learning curriculum, 2013.